Enhancing Health and Public Health through Machine Learning: Decision Support for Smarter Choices - Rodrigues, Pedro Miguel; Madeiro, João Paulo; Marques, João Alexandre Lobo (Bioengineering, 2023)
In recent years, the integration of Machine Learning (ML) techniques in the field of healthcare and public health has emerged as a powerful tool for improving decision-making processes [...]
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: n/a

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.